2015
DOI: 10.1016/j.msea.2015.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafine processing of (TiB+TiC)/TC18 composites processed by ECAP via Bc route

Abstract: Equal channel angular pressing provides a convenient approach to introduce ultrafine grain size into commonly used metallic materials. In this study, equal channel angular pressing of (TiB+TiC)/TC18 composite was carried out under different passes via route Bc. Microstructure evolution is systematically investigated by optical microscope (OM), scanning electron microscope (SEM), and transmission electron microscope (TEM). The results show that grain boundary sliding contributes much to the plastic deformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Compared with coarse‐grained materials, ultrafine‐grained materials (in submicron or nanometer) often have good physical and chemical properties, such as higher hardness, higher strength, longer fatigue life, and better low‐temperature superelasticity . Some ultrafine‐grained materials even exhibit good thermostability, high corrosion resistance, high wear resistance, and excellent biocompatibility .…”
Section: New Preparation Methods Of Ti Alloys For Biomedical Applicatmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with coarse‐grained materials, ultrafine‐grained materials (in submicron or nanometer) often have good physical and chemical properties, such as higher hardness, higher strength, longer fatigue life, and better low‐temperature superelasticity . Some ultrafine‐grained materials even exhibit good thermostability, high corrosion resistance, high wear resistance, and excellent biocompatibility .…”
Section: New Preparation Methods Of Ti Alloys For Biomedical Applicatmentioning
confidence: 99%
“…As such, the ultrafine‐grained materials are expected to be the next generation of biomedical materials. So far, many different severe plastic deformation (SPD) methods have been proposed, including equal channel angular extrusion (ECAP) and accumulative roll bonding (ARB), high‐pressure torsion (HPT), multi‐directional forging, twist extrusion, cyclic‐extrusion–compression, friction stir processing (FSP) …”
Section: New Preparation Methods Of Ti Alloys For Biomedical Applicatmentioning
confidence: 99%
“…It is well known that ultrafine‐grained materials, which have the grain sizes in submicron or nanometer, often exhibit enhanced mechanical properties, corrosion resistance, and biocompatibility compared with their coarsening‐grained counterparts . Ultrafine‐grained materials generally can be obtained by severe plastic deformation .…”
Section: Advanced Surface‐modification Methodsmentioning
confidence: 99%
“…In their investigation, Lu et al (2017) also found that four ECAP passes of (TiB + TiC)/Ti6Al4V composite were sufficient to produce homogeneous dispersion of TiB and TiC particles in the ultrafine grain structure. Significant grain refinements (100 nm) were attainted when 0.2 per cent B 4 C was added to (TiB + TiC)/TC18 and processed in two passes by ECAP (Wang et al , 2015c). However, sufficient recrystallization was achieved after the third pass.…”
Section: Development Of High Strength Near-α Titanium Alloysmentioning
confidence: 99%